Connect - Gough, Julian, 1966- (Picador, 2018)
"In a world run by computers, hackers have power--and awkward, homeschooled Colt is among the best. But when Colt secretly submits his mother Naomi's breakthrough research to a biotech conference, and it is immediately shut down, mother and son are forced to go on the run. Now Colt is coding for his life. As the military, and Colt's father, hunt them through a Las Vegas of self-driving cars and surveillance drones, Naomi has to decide how far she will go to protect her child. Can she kill a man? Can she destroy the world? And Colt is finally forced to leave the comfort of virtual reality and face his greatest terror: love"--